ANALISIS DAN PERANCANGAN USER INTERFACE/ USER EXPERIENCE APLIKASI MNC TRADE NEW MENGGUNAKAN METODE DOUBLE DIAMOND PADA PT. MNC SEKURITAS - Iqbal Priswara; Tri Sagirani; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
PT MNC Sekuritas, the name MNC is an abbreviation of the word Media Nusantara Citra. PT MNC Sekuritas itself is a securities company that was founded in 1989 and is under the auspices of PT MNC Kapital Indonesia Tbk and has now developed into a local securities company that is committed to responding to the needs of the Indonesian people. One of the applications used by PT MNC Sekuritas is MNC Trade New , an application that is used to trade stocks and also monitor stock movements that can be used on mobile operating systems such as Android and iOS. There are several problems regarding the appearance of MNC Trade New, namely the design that is less than optimal and seems ordinary, as well as the user's desire to make transactions faster, then there are menu buttons that are too small, and the display of stock charts that are deemed unattractive. The double diamond method is a solution for analyzing and designing the ui/ux display of the MNC Trade New application with usability testing that focuses on 3 measurement aspects, namely learnability, efficient, and satisfaction using success rate, time based efficiency and SUS questionnaire calculations. With 10 samples of customer application users, the results obtained are 100% learnability, efficieny 0.027 goals/sec, and the SUS score obtained an average value of 80.